Pengaruh Pengelolaan Kelas Oleh Guru Terhadap Motivasi Belajar PAK Siswa Kelas IX SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Yulandari D Rajagukguk; Oktober Tua Aritonang; Dame Taruli; Rida Gultom; Pestaria Naibaho (LPPM Politeknik Pratama, 2023)
The aim of this research is to determine the positive and significant influence of classroom management by teachers on the PAK learning motivation of class IX students at SMP Negeri 4 Tarutung for the 2023/2024 academic year. The research method used is a quantitative research method with a One Shot Case Study experimental approach. The population is all class IX students of SMP Negeri 4 Tarutung for the 2023/2024 academic year, totaling 103 people and a research sample of 30 people was determined using the Nonprobability Sampling technique, namely Purposive Sample. Data was collected using a positive closed questionnaire with 16 items for variable : 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.573 > rtabel(a=0,05,n=30) = 0.361. b) Testing a significant relationship obtained tcount= 3. > ttabel(a=0,05,dk=n-2=28)= 2.048. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 32.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=13, dk denominator=n-2=30-2=28) namely 13.67 > 2.09. Thus, Ha, that is, there is a positive and significant influence of classroom management by teachers on the learning motivation of PAK students in class IX of SMP Negeri 4 Tarutung for the 2023/2024 academic year is accepted and H0 is rejected.